Chronic Progressive Encephalitides - J Gordon Millichap (Pediatric Neurology Briefs, 1998)
An excellent review of chronic progressive encephalitides of childhood (CPEC), with particular emphasis on the prototypical disease, subacute sclerosing panencephalitis (SSPE), is presented from the Institute for Research in Childhood Neurodegenerative Diseases, and University of South Alabama, Mobile, AL.